Pengaruh Pemberian Cendawan Mikoriza Arbuskula terhadap Pertumbuhan dan Produksi Rumput Setaria splendida Stapf yang Mengalami Cekaman Kekeringan - P. D M H Karti (Media Peternakan, 2004)
The limited water can cause drought stress, which can affect the growth and plant yield. One of the efforts to maintain plant water status under drought stress is by using mycorrhizal. The objective of this research was to assay the effect of Arbuscular Mycorrhizal Fungi (AMF) on growth and production of Setaria splendida under drought stress. The experiment was conducted in Laboratory of Agrostology greenhouse, Faculty of Animal Science, Bogor Agricultural University. The experiment was designed in completely randomized design with two factors (2 x 5) and 3 replications. The first factor was mycorrhizal treatment (Mo= without AMF, M1 = with AMF) and the second factor was level of soil water content (A1 = 100% of field capacity, A2 = 85% of field capacity, A3 = 70% of field capacity, A4 = 55% of field capacity, A5 = 40% of field capacity). The result showed that the effect of AMF inoculation was significantly increased (P < 0.05) dry weigth of shoot and very significantly (P < 0.01) leaf area and transpiration rate. The water treatment was significantly decreased (P < 0.05) vertical heigth, tiller number, dry weigth of shoot and root, transpiration rate, but significantly improved water used efficiency. The interaction effect between AMF and water treatment were not significantly different. The growth and plant production were decreased with lower of water content of soil. If compared between AMF treatment with non-AMF treatment, the growth dan plant production were better than AMF treatment. Key words: forage, Setaria splendida, Arbuscular Mycorrhizal Fungi, drought stress